Animal Husbandry and Faunal Material: Integrating Data from Finland (AD 1200–1800) - Bläuer, Auli (Taylor & Francis, 2022)
This paper is a synthesis of zooarchaeological evidence from 27 medieval and post-medieval sites from Finland. These faunal samples derive from rural, town, manor, castle and ecclesiastic sites, and their production and consumption patterns were examined by studying the role of the major domesticates (cattle, sheep, goats and pigs). As taxonomic abundance in faunal material may be altered by taphonomic processes, such as burning, these factors were assessed before comparison. The animal husbandry system in Finland was shaped by environmental constraints that limited the number of animals that could be kept over winter. However, some specialisations were observed within the frame of the basic pattern. This paper demonstrates the usefulness of zooarchaeological data in the study of animal husbandry and consumption and production patterns. These findings support data integration as a useful tool for understanding general large-scale processes, such as urbanisation, development, environmental adaptation and the specialisation of animal production.